Influence of water hardness on functional and sensory quality of cold infused robusta coffee leaf tea - Kiki Fibrianto; Sudarminto Setyo Yuwono; Devy Sekarlianty (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
Cold infused technique is one of the brewing methods that potentially able to preserve coffee leaf tea functional properties. It is mainly attributed to the absence of heat treatment during its processes.  However, without involving heat, the sensory quality of cold brewing tea is generally weak. To overcome this issue, it was hypothesized that water quality used for the brewing is important to govern optimum functional properties of Robusta coffee leaf tea and at the same time to maintain its sensory quality. In this current study, Response Surface Methodology (RSM) was applied by implementing Box-Behnken Design (BBD) to optimize both total phenolic content (TPC) and antioxidant activity by modifying length and temperature of cold brewing as well as its water and coffee leaf powder ratio.  There were 3 different commercial drinking water used for brewing to represent 3 different hardness level of water. All optimum brewed coffee leaf tea was then sensorially evaluated by Rate All That Apply (RATA) method. It was found that level of water hardness is positively correlated to TPC but negatively correlated to brewing temperature as well as water and coffee leaf powder ratio. It was also found that the higher level of water hardness, both fruity and marine aroma tended to be more intense (p-value<0.05). Meanwhile the lower level of water hardness tended to enhance sweet aroma and astringent mouth-feel (p-value<0.05) of cold infused coffee leaf tea.